Review of the genus Cavatorium Dlabola, 1980 (Hemiptera: Auchenorrhyncha: Issidae), with description of a new species from Iran - Gnezdilov, Vladimir M.; Mozaffarian, Fariba (Zootaxa, 2021)
Examination of the materials on Cavatorium dumetorum (Dlabola, 1981), including the type specimens, revealed that Dlabola (1981) based his description of this species on mixed type series. C. dumetorum sensu stricto is clearly distinguished by male anal tube with latero-apical processes and ventral phallobase lobe narrowing apically. Another species, externally close to C. dumetorum, but well recognized by male anal tube without processes and ventral phallobase lobe not narrowing apically, is described as new basing on the paratypes of C. dumetorum and other material available. C. dumetorum is re-described and a key to species of the genus is provided.